CRITIC TOWARD THE NEW POLITIC OF ISLAM; PAN-ISLAMISME - Sitti Nurtina (Universitas Muhammadiyah Yogyakarta, 2019)
AbstractThis journal describes the criticism of the new politic view of Islam known as Pan-Islamic, using a book from Naveed S. Sheiks as a reference to be studied through analysis of epistemological and ontological aspects. Judging from its development, this understanding has experienced various obstacles, starting from the lack of purity of the understanding as a result of Western influence, unclear legitimacy of the container or organization that carries the understanding, and the methods used are still traditional. This has led to much speculation, especially criticism from several prominent Muslim scholars, including the writer himself. The criticism came from Naveed S. Siiks himself who assumed that politics run by the pan-Islamic sometimes did not conclude an act of courage, sometimes even dictated by the west. Meanwhile, Mohammed Arkoun thinks that there must be a renewal of a very traditional Pan Islamism in making policies for its member countries, there is stiffness in conducting international relations so that it has not been able to answer the problems experienced by contemporary Muslim societies and still not be a place to channel aspirations and mission noble to unite Muslims throughout the world. Arkoun's learning model is known as' Applied Islam.Keywords : Criticism, New Politic, Pan Islamism.